IncX3 plasmid mediated occurrence of blaNDM-4 within Escherichia coli ST448 from India - Nargis A. Choudhury; Deepjyoti Paul; Atanu Chakravarty; Amitabha Bhattacharjee; Debadatta Dhar Chanda (Elsevier, 2018)
This study was designed to investigate blaNDM-4 encoded within IncX3 type plasmid and their copy number alteration under carbapenem pressure within clinical isolates of Escherichia coli. NDM-4 producing E. coli isolates were collected from an Indian hospital and transferability as well as plasmid incompatibility typing was determined. Genetic environment and antibiogram profiling was carried out. Quantitative Real Time PCR was done to determine the change in plasmid copy number under concentration gradient carbapenem stress. Multilocus sequence typing and pulsed field gel electrophoresis was performed for typing of isolates. Four multidrug resistant isolates were found to harbour transconjugable blaNDM-4 carrying within IncX3 type plasmid. The blaNDM-4 was flanked by insertion sequences ISAba125 and IS5 in the upstream region whereas bleMBL was present in the downstream area. Copy number results indicated that the blaNDM-4 gene was maintained high in plasmid under exposure of ertapenem. All the strains belonged to ST448 and PFGE analysis revealed three different pulsotypes. This is the first report of blaNDM-4 encoded IncX3 type plasmid in E. coli of ST448 and needs a systematic screening policy to rapid detection of NDM-4 poducing strains to prevent dissemination of this resistant determinant in future. Keywords: New-Delhi metallo-β-lactamase, Horizontal transferability, Plasmid, Copy number